2014
DOI: 10.1523/jneurosci.0383-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Contributing to TARP Regulation of Channel Conductance and Polyamine Block of Calcium-Permeable AMPA Receptors

Abstract: Many properties of fast synaptic transmission in the brain are influenced by transmembrane AMPAR regulatory proteins (TARPs) that modulate the pharmacology and gating of AMPA-type glutamate receptors (AMPARs). Although much is known about TARP influence on AMPAR pharmacology and kinetics through their modulation of the extracellular ligand-binding domain (LBD), less is known about their regulation of the ion channel region. TARP-induced modifications in AMPAR channel behavior include increased single-channel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 40 publications
(28 reference statements)
4
42
0
Order By: Relevance
“…The proximal end of the C‐terminal region of the TARP, γ‐2 or stargazin, has been shown to attenuate polyamine block of AMPARs through a mechanism that involves a direct interaction with the intracellular domain of GluA1 or GluA4 subunits (Soto et al . ). A similar finding has been reported with Neto2, where positive residues in the proximal intracellular C‐terminal domain are implicated in reducing polyamine block (Fisher & Mott, ).…”
Section: Discussionmentioning
confidence: 97%
“…The proximal end of the C‐terminal region of the TARP, γ‐2 or stargazin, has been shown to attenuate polyamine block of AMPARs through a mechanism that involves a direct interaction with the intracellular domain of GluA1 or GluA4 subunits (Soto et al . ). A similar finding has been reported with Neto2, where positive residues in the proximal intracellular C‐terminal domain are implicated in reducing polyamine block (Fisher & Mott, ).…”
Section: Discussionmentioning
confidence: 97%
“…In mammals, stargazin is known to alter the number of functional AMPA receptors at a synapse (Chen et al, ; Tomita et al, ; Bats et al, ; Milstein and Nicoll, ; Jackson and Nicoll, ; Matsuda et al, ; Studniarczyk et al, ; Soto et al, ). To examine this we first evaluated the mEPSC amplitude by binning the amplitudes and plotting their distribution as shown in [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This family of proteins includes several members, and namely γ-3, -4, -5, -7, -8 [96,97] , varying in their influence on AMPAR characteristics and manifesting different, although partially overlapping, distribution patterns throughout the CNS. Native AMPARs are thought to be composed of one to four TARPs together with their core pore-forming subunits; however, it is commonly accepted that only one type of TARP is expressed within a specific AMPAR complex [98][99] . TARP assembling influences various fundamental aspects of AMPAR activities thus modifying the neuronal trafficking abilities of GluR2-containing AMPARs.…”
Section: Potential Targets (And Future Perspectives) For the Treatmenmentioning
confidence: 99%
“…TARP assembling influences various fundamental aspects of AMPAR activities thus modifying the neuronal trafficking abilities of GluR2-containing AMPARs. In particular it has been shown that TARPs are engaged in the subunit-specific trafficking of AMPARs, which by modulating the expression of specific AMPAR complexes [99] together with augmented single channel conductance and impaired block of GluR2-lacking AMPARs by endogenous intracellular polyamines tend to increment the molecular complexity operating during stress-related neuronal disorders [98] .…”
Section: Potential Targets (And Future Perspectives) For the Treatmenmentioning
confidence: 99%